Antibiotic Resistance Patterns of Uropathogens Isolated from Patients with Urinary Tract Infections at Kathmandu Medical College, a Tertiary Care Hospital in Nepal - Chaudhary, Anup; Joshi, Suresh; Kafle, Anjina; K.C., Ganesh; Thapa, Himadri (Nexus: Journal of Interdisciplinary Engineering, Technology and Management, 2026)
Urinary tract infection (UTI) is one of the most common bacterial infections globally, with increasing prevalence and rising antimicrobial resistance posing major challenges in clinical settings. Nepal continues to report a significant burden of UTIs, particularly among females and individuals of reproductive age. The purpose of the present research was to ascertain the urinary pathogenic bacterial profiles, antimicrobial susceptibility patterns, prevalence, and demographic distribution of patients suspected of having UTIs at Kathmandu Medical College Public Limited. A total of 151 urine samples were collected from patients with UTI symptoms. Samples were sent to the Microbiology Laboratory at Himalayan White House International College, where they were cultured, identified, and tested for antibiotic susceptibility using conventional microbiological techniques. Significant bacterial growth was found in 51 (33.77%) of the 151 samples examined. Males showed a lower prevalence (21.57%) than females (40%). The age group of 21 to 30 years old had the largest number of UTI cases. The most common pathogen was Escherichia coli (33.33%), followed by Pseudomonas aeruginosa (17.64%) and Klebsiella pneumoniae (13.70%). The isolates showed high resistance to ceftazidime and cefaclor, while the highest susceptibility was observed to amikacin and piperacillin-tazobactam. Notably, multidrug resistance was identified in 66.7% of uropathogenic isolates, including E. coli, Klebsiella spp., and Pseudomonas spp. showing the highest prevalence. The study shows that UTIs are common, especially among young adult women. The predominance of E. coli and high-level resistance to widely used antibiotics underscore the importance of routine culture and sensitivity testing for successful treatment. These results highlight the critical need in Nepali healthcare settings for improved antimicrobial stewardship, regular monitoring of resistance trends, and ongoing updates to empiric therapy recommendations. Controlling the rising incidence of UTIs and preventing the development of resistant uropathogens also depend on incorporating routine culture-based diagnosis, encouraging doctors to use antibiotics sensibly, and raising public awareness of the dangers of self-medication. For doctors, microbiologists, and public health policymakers, this study offers up-to-date, hospital-based data on UTI prevalence and resistance rates in Kathmandu.